Amides as cryoprotectants for freezing stallion semen: A review - Alvarenga, Marco Antonio [UNESP]; Papa, Frederico Ozanam [UNESP]; Landim-Alvarenga, F. C.; Medeiros, ASL (Elsevier B.V., 2005)
Stallion semen cryopreservation, despite its impact on the horse industry, is not an established technology. During the last years, a number of modifications have been proposed to the freezing process, however, a large population of stallions still have poor semen quality and fertility after frozen-thawed. Glycerol toxicity could be a reason for the variation on stallion sperm freezability. There are limited publications concerning the use of alternative cryoprotectants for equine sperm. Glycerol is contraceptive for some species and other cryoprotectors, such as amides, have been show to be a good option for freezing semen of these species. Recent reports have shown encouraging data respecting the use of amides as cryoprotectants for stallions, with more remarkable improvements for semen from stallions that freeze poorly when glycerol is used. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: amides; cryoprotectants; freezing stallion semen